Spectral re-evaluation of sediment thickness within Afikpo Basin and environs, southeastern Nigeria, using high resolution aeromagnetic dataset - Stephen Onyejiuwaka Ibe, Stephen; Uche Iduma, Kevin (International Journal of Advanced Geosciences, 2020)
The discovery of hydrocarbon in the areas bordering Afikpo Basin prompted the re-evaluation of the sedimentary thickness within the basin with high resolution geophysical data. Depth to magnetic sources, sediment thickness, basement topography and structures within it were investigated using spectral analysis, analytic signal and tilt derivative of aeromagnetic data. The results show that the depth to the basement varies between 1.52 and 3.15 km; depth to intermediate magnetic anomaly sources ranges from 0.40 to 1.05 km and depth to the shallow sources varies from 0.10 to 0.34 km. Structures within the basin predominantly have NE-SW trend and the boundary between Afikpo Basin and Southwestern Basement Massif is characterised by NE-SW trending dykes with the longest dyke extending from Amasiri to Abba Omege. The results show that the basin is greatly undulated and the deformation that led to its undulation resulted in the formation of structures which could serve as traps for hydrocarbon accumulation. Sediment thickness greater than 2.3 km associated with some locations within the basin prompted the classification of the places as viable for hydrocarbon formation, if other conditions necessary for its generation are favourable. These places were recommended for further studies for hydrocarbon prospecting on the bases of their sediment structural complexities and thicknesses.Â Â